Study on the effects of pre-slaughter transport stress on water holding capacity of pork: Insights from oxidation, structure, function, and degradation properties of protein - Chao Ma; Jian Zhang; Ruyu Zhang; Lei Zhou; Laixue Ni; Wangang Zhang (Food Chemistry: X)
This work systematically investigated the effects of pre-slaughter transport stress on pork water holding capacity (WHC) during aging from the perspectives of oxidation, structure, function, and degradation properties of protein. Pigs were randomly divided into three-hour transport (Transport-induced stress, T group) and three-hour transport followed by three-hour resting (Control, TR group). Results demonstrated that T treatment markedly declined pork WHC. Compared with TR group, T group presented increased oxidation levels. Meanwhile, T treatment exacerbated the shift of protein secondary structure from α-helix to random coil and protein unfolding levels. The decreased solubility, thermal stability, and degraded levels of proteins were also observed in T group. Additionally, muscle contractions of T group were more severe than TR group. This study supported that pre-slaughter transport stress altered physicochemical properties and structures of postmortem muscle proteins, which reduced pork WHC via impairing the interactions between protein and water molecules and changing the muscle fiber structure.